Transformasi Pembelajaran Sejarah dalam Konteks Pendidikan Abad 21: Sejarah Perkembangan dan Implementasi Model Pembelajaran Inovatif - Sofiia Muntazza; Suhendro Suhendro; Syarfira Syarfira; Sani Safitri; Rani Oktapiani (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2025)
The transformation of history learning in the context of 21st-century education aims to prepare students to face the challenges of an increasingly complex and dynamic world. The concept of 21st-century learning emphasizes the development of critical, collaborative, and creative skills, which are highly relevant to studying history. History learning in the 21st century must include a more interactive approach, utilizing technology as a tool to deliver historical material in a more engaging and relevant manner. Through innovative models such as project-based learning and inquiry learning, students can be more actively involved in the learning process, not only receiving information but also developing the ability to analyze, evaluate, and draw conclusions from various historical sources. Technology supports the creation of more engaging learning experiences, such as the use of multimedia, simulations, and other digital resources. Furthermore, teachers play a role as facilitators, helping students build historical awareness, guiding them in seeking information, and developing critical thinking skills. However, the implementation of this learning model faces various challenges, such as limited technological infrastructure and a lack of teacher training. Therefore, efforts are needed to strengthen teacher competencies and adapt the curriculum to be more adaptive to changing times.